THE EFFECT OF BRAND IMAGE AND PRODUCT QUALITY ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE (STUDY ON IM3 USERS IN SEMARANG CITY) - Dhiya Alya Kasamira; Widayanto Widayanto; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2024)
The high demand for information and communication on the internet has made the telecommunications industry experience rapid growth. This growth encourages every company to be able to meet consumer needs with the right strategy, one of which is by building a brand image and improving product quality. That way, it is expected to be able to create satisfaction in consumers and encourage loyalty in the future. This study aims to determine the effect of brand image and product quality on consumer loyalty through customer satisfaction for IM3 users in Semarang City. The type of research is explanatory research, using nonprobability sampling and purposive sampling for data collection. The sample collected was 100 respondents. The study used Partial Least Square analysis techniques, estimated by the SmartPLS 4.0 program. The results of the analysis show that the results of testing direct and indirect effects are positive and significant results. Based on the results of the mediation test with the VAF method, customer satisfaction is a partial intervening variable in mediating the effect of brand image on customer loyalty, and customer satisfaction is a partial intervening variable in mediating the effect of product quality on customer loyalty.Keywords: Brand Image, Consumer Loyalty, Consumer Satisfaction, Quality ProductKebutuhan informasi dan komunikasi yang tinggi terhadap internet saat ini menjadikan industri telekomunikasi mengalami pertumbuhan pesat. Pertumbuhan ini mendorong setiap perusahaan untuk mampu memenuhi kebutuhan konsumen dengan strategi yang tepat, salah satunya dengan membangun brand image dan meningkatkan kualitas produknya. Dengan begitu, diharapkan mampu tercipta kepuasan pada konsumen dan mendorong loyalitas di masa mendatang. Penelitian ini bertujuan untuk mengetahui pengaruh brand image dan kualitas produk terhadap loyalitas konsumen melalui kepuasan konsumen pada pengguna IM3 di Kota Semarang. Tipe penelitian adalah explanatory research, menggunakan nonprobability sampling dan purposive sampling untuk pengumpulan data. Sampel yang dikumpulkan 100 responden. Penelitian menggunakan teknik analisis Partial Least Square, diestimasi program SmartPLS 4.0. Hasil analisis menunjukkan bahwa hasil pengujian pengaruh langsung dan tidak langsung adalah hasil yang positif dan signifikan. Berdasarkan hasil uji mediasi dengan metode VAF, kepuasan konsumen merupakan variabel intervening parsial dalam memediasi pengaruh brand image terhadap loyalitas konsumen, serta kepuasan konsumen merupakan variabel intervening parsial dalam memediasi pengaruh kualitas produk terhadap loyalitas konsumen.Kata Kunci: Brand Image, Loyalitas Konsumen, Kepuasan Konsumen, Kualitas Produk